Financial accounting : information for decisions - Wild, John J. (Boston, Massachusetts : McGraw Hill Education, 2008)
Addresses the topics and issues typically covered in "Financial Accounting" while at the same time using entrepreneurial examples, application of analysis skills, integration of interactive tutorial software, and a pedagogical design. This book integrates ideas and practices followed by business entrepreneurs.
Accounting in business -- Accounting for transactions -- Preparing financial statements -- Accounting for merchandising operations -- Accounting for inventories -- Internal controls and accounting for cash -- Accounting for receivables -- Accounting for long-term assets -- Accounting for current liabilities -- Accounting for long-term liabilities -- Accounting for equity -- Accounting for cash flows -- Interpreting financial statements
Includes index.
Keywords: ACCOUNTING